Вы находитесь на странице: 1из 37

EC270: Microeconomic Theory I

.

Chapter 2 Mathematics for Microeconomics

Dr. Logan McLeod, PhD

Wilfrid Laurier University, School of Business & Economics

September 4, 2014

for Microeconomics Dr. Logan McLeod, PhD Wilfrid Laurier University, School of Business & Economics September 4,

Functions

Function: describe the relationship between input and output variables For each input (independent) variable ‘x’, a function assigns a unique number to the output (dependent) variable ‘y ’ according to some rule

y =

y = x 2

2x

we may want to indicate y depends x without a specific algebraic relationship:

y = f(x)

Frequently, y depends on several variables (x 1 , x 2 ,

We write y = f (x 1 , x 2 ,

, x n )

, x n )

depends on several variables ( x 1 , x 2 , We write y = f

Graphs

Graph: depicts the behaviour of a function pictorially

x is usually on the horizontal axis

y is depicted on the vertical axis

in economics, it is common to graph functions with the independent variable on the vertical axis and the dependent variable on the horizontal axis

e.g. demand functions

Figure: (A.1) Graphs of functions

vertical axis and the dependent variable on the horizontal axis e.g. demand functions Figure: (A.1) Graphs
vertical axis and the dependent variable on the horizontal axis e.g. demand functions Figure: (A.1) Graphs

Properties of Functions

Continuous function: can be drawn without lifting a pencil from the paper

there are no jumps in a continuous function

Smooth function: has no “kinks” or corners

Monotonic function: always increases or always decreases

a positive monotonic function always increases as x increases

a negative monotonic function always decreases as x increases

positive monotonic function always increases as x increases a negative monotonic function always decreases as x

Inverse Functions

Recall:

A function assigns a unique number y for each x

A monotonic function is always increasing or always decreasing Thus, a monotonic function will have a unique value of x associated

with each value of y Inverse function: a function assigns a unique number x to each y

For example, y = 2x:

y = 2x

x = y

2

inverse function exists: a unique value of x is associated with each value of y

What about y = x 2

y = x 2

x = ± y

inverse function does not exist: not a unique value of x associated with each value of y

x 2 ⇒ x = ± √ y inverse function does not exist : not a

Equations and Identities

Equations asks when a function is equal to some particular number.

Equation

= 8

= 9

f(x) = 0

2x

x 2

Solution

x

x

x = x

= 4

= 3 or x = 3

Solution: a value of x satisfying the equation

Identity: a relationship between variables that holds for all values of the variables

(x + y) 2

x 2 + 2xy + y 2

2(x + 1)

2x + 2

The symbol ‘’ means that the left-hand side and the right-hand side are equal for all values of the variables

2 The symbol ‘ ≡ ’ means that the left-hand side and the right-hand side are

Linear Functions

Linear function: a function of the form y = mx + b

where m and b are constants

They can also be expressed implicitly: ax + cy = d

we would often solve for y as a function of x , to convert this to the standard form

y = d a

c

c x

= d we would often solve for y as a function of x , to convert

Changes and Rates of Change

The change in x: x

A change in x from x 1 to x 2 is x = x 2 x 1

Marginal change: very small changes in x we are generally interested in only very small changes in x

Rate of change: the ratio of two changes assume y = f (x) then the rate of change of y with respect to x is

y

= f(x + ∆x) f(x)

x

x

) then the rate of change of y with respect to x is ∆ y =

Changes and Rates of Change

y

= f(x + ∆x) f(x)

x

x

Note:

for a linear function (y = mx + b) has a constant rate of change of y with respect to x:

y

= [b + m(x + ∆x)] [b + mx]

= mx

x

x

x

= m

for a non-linear function, the rate of change will depend on the value of x. For example y = x 2 :

y

[(x + ∆x) 2 ] [x 2 ]

=

x

x

= x 2 + 2xx + (∆x) 2 x 2

x

= 2x +∆x

∆ x ) 2 ] − [ x 2 ] = ∆ x ∆ x =

Slopes and Intercepts

Slope of the function is the rate of change of y as x changes we commonly interpret the rate of change of a function graphically as the slope of the function

For example:

y

= 5 x + 5

3

vertical intercept: the value of y when x = 0 (which is y = 5)

horizontal intercept:

the value of x when y = 0 (which is x = 3)

slope is 5

3

6

5 4 3 2 1 0 0 1 2 3
5
4
3
2
1
0 0
1
2
3

4

X Axis

intercept : the value of x when y = 0 (which is x = 3) slope

Slopes and Intecepts

if a linear function has the standard form y = mx + b, then

vertical intercept horizontal intercept slope

b

b

m

m

if a linear function has the form: ax 1 + cx 2 = d, then

vertical intercept

horizontal intercept

slope

d

c d

a

a

c

cx 2 = d , then vertical intercept ⇒ horizontal intercept ⇒ slope ⇒ d c

Slopes and Intercepts

A nonlinear function has the property that its slope changes as x changes

A tangent to a function at some point x is a linear function that has the same slope

Example:

If y whenever x , then y will always have the same sign as x (slope will be positive)

If y () whenever x (), then y and x will have opposite signs (slope will be negative)

Figure: (A.2B) slope of y = x 2 at x = 1

∆ y and ∆ x will have opposite signs (slope will be negative) Figure: (A.2B) slope
∆ y and ∆ x will have opposite signs (slope will be negative) Figure: (A.2B) slope

Absolute Values and Logarithms

Absolute value of a number |x| is a function f (x) defined by:

f(x) = ( x x

if x

if x

0

< 0

Logarithm (or log) of x describes an inverse function of the exponential function f (x) = a x : y = log x or y = log(x)

a logarithm of base ‘a’ is an inverse function of: f (x) = a x the exponent to which base ‘a’ must be raised to give x. if f (x) = a x , the log a (x) is the exponent to which base a must be raised to give x the ‘natural log’ of x is ln(x), which has base e (i.e., e x )

Properties of the logarithm:

ln(xy ) = ln(x) + ln(y )

ln y « = ln(x) ln(y )

x

for all positive numbers x and y

for all positive numbers x and y

ln(e) = 1

e = 2.7183

ln(x y ) = y ln(x)

numbers x and y for all positive numbers x and y ln ( e ) =

Derivatives

Derivatives

Derivatives

Derivative is the limit of the rate of change of y with respect to x as the change in x goes to zero

gives precise meaning to the phrase “the rate of change of y with respect to x for small changes in x

for y = f (x), the derivative (f (x)) is:

df (x)

dx

=

lim

x0

f(x + ∆x) f(x)

x

Derivatives of Linear Functions

Recall, the rate of change of y = mx + b is a constant (m)

Thus, if f (x) = mx + b then

df (x)

dx

= m

Recall, the rate of change of y = mx + b is a constant ( m

Derivatives

Derivatives of Non-Linear Functions recall the rate of change of y with respect to x will usually depend on x

for example: y = x 2 y = 2x + ∆x

x

the derivative of y with respect to x will be a function of x:

df (x)

dx

Useful derivatives to know:

=

lim

x0 2x + ∆x = 2x

 

Family

f (x)

df (x)

dx

Constant

c

0

Power

x c

cx c1

Exponential

e

x

e x

   

1

 

Logarithmic

ln x

x

x c cx c − 1 Exponential e x e x     1   Logarithmic

The Power Rule

Assume: f (x) = cx α , where c and α are constants

then

df (x)

dx

= cαx α1

“multiply x by its exponent and subtract one from the exponent you began with to find the derivative.”

Example: if f (x) = x 3 , what is df (x) ?

dx

exponent you began with to find the derivative.” Example : if f ( x ) =

The Product Rule

Assume: g(x) and h(x) are both functions of x

define f (x) = g(x)h(x) (i.e., the product of two functions)

then

df (x)

dx

=

g(x) dh(x) + h(x) dg(x)

dx

dx

“the first times the derivative of the second, plus the second times the derivative of the first”

Example: if g(x) = x 2 and h(x) = x 2 + 3, what is df (x) ?

dx

of the first” Example : if g ( x ) = x 2 and h (

The Chain Rule

Composite function:

given two functions y = g(x) and z = h(y ) the composite function is f (x) = h(g(x))

Chain Rule: the derivative of a composite function, f (x), with respect to x is

 

df (x)

dh(y )

dg(x)

 

=

 

dx

dy

dx

Example:

Assume

Then

g(x)

h(y)

f(x)

=

=

=

x 2 =

2y + 3 2x 2 + 3

y

dg(x)

dx

dh(y )

dy

df (x)

dx

=

=

=

2x

2

2 2x = 4x

) f ( x ) = = = x 2 = 2 y + 3 2

Second Derivatives

Second derivative of a function:

the derivative of the derivative of that function

 

if

then the 1 st

derivative

is

then the 2 nd

derivative

is

y = f (x)

df (x)

dx

or f (x)

d 2 f(x)

dx 2

or f (x)

measures the curvature of a function

2 nd derivative

implies f (x) is

f (x) < 0 f (x) > 0 f (x) = 0

concave near that point (slope is decreasing) convex near that point (slope is increasing) flat near that point (possible inflection point)

(slope is decreasing) convex near that point (slope is increasing) flat near that point (possible inflection

Partial Derivatives

Assume z = f (x, y )

Partial derivative of f (x, y ) with respect to x is just the derivative of the function with respect to x, holding y fixed:

f(x, y)

x

= lim

x0

f(x + ∆x, y) f(x, y)

x

Similarly, the partial derivative with respect to x 2

f(x, y)

y

= lim

y0

f(x, y + ∆y) f(x, y)

y

Partial derivatives have exactly the same properties as ordinary derivatives

( x , y + ∆ y ) − f ( x , y ) ∆

Example: Partial Derivatives

Assume a Cobb-Douglas function:

f(x, y) = x α y 1α

Partial Derivative, with respect to x

Use the power rule to get f(x,y) :

x

f(x, y)

x

= αx α1 y 1α = α y

x

1α

Second Partial Derivative, with respect to x

2 f(x, y)

x 2

= α(α 1)x α2 y 1α

Cross Partial Derivative, of f(x,y) with respect to y

x

2 f(x, y)

xy

= α(1 α)x α1 y α

x , y ) with respect to y ∂ x ∂ 2 f ( x ,

Young’s Theorem

Young’s Theorem: the order in which partial differentiation is conducted to evaluate second-order partial derivatives does not matter.

f ij = f ji

for any pair of variables x i , x j .

Example: f (x 1 , x 2 ) = x x

1

2

3

2

f 1 =

3

2

2x 1 x

2

f 12 = 6x 1 x

2

2

1

f 2 = 3x

2

x

2

2

f 21 = 6x 1 x

2

x x 1 2 3 2 f 1 = 3 2 2 x 1 x 2

Total Differentiation

Totally differentiating a function:

Tells us the total change in a function from a combined change in x and y .

Describes movement along a curve.

df (x, y ) = f(x, x y)

dx + f(x, y) y

dy

Interpretation of Total Differentiation:

The partial derivatives f(x,y)

x

and f(x,y)

y

indicate the

rate of change in the x and x directions

dx and dy are the changes in x and y

∂ f ( x , y ) ∂ y indicate the rate of change in the

Optimization

Optimization

Optimization - One Variable

Optimization refers to the process of finding the largest value (maximum) or the smallest value (minimum) a function (y = f (x)) can take.

Maximum: f (x) achieves a maximum at x if f(x ) f (x) for all x It can be shown that if f (x) is a smooth function that achieves its maximum value at x , then:

First-order condition:

Second-order condition:

df (x ) = 0

dx

(the slope of f (x) is flat at x )

d 2 f(x )

0

dx 2 (f (x) is concave near x )

f ( x ) is flat at x ∗ ) d 2 f ( x ∗

Optimization - One Variable

Minimum: f (x) achieves a minimum at x if f (x ) f (x) for all x

It can be shown that if f (x) is a smooth function that achieves its maximum value at x , then:

First-order condition:

Second-order condition:

df (x )

dx

= 0

d 2 f(x )

0

dx 2 (f (x) is convex near x )

: d f ( x ∗ ) dx = 0 d 2 f ( x ∗

Optimization - Multiple Variables

Multivariate Case: if y = f (x 1 , x 2 ) is a smooth function that achieves

a maximum or minimum at some point (x

), then we must satisfy:

, x

1

2

f(x

1

,

2

x

)

x 1

,

f(x

1

2

x

)

x 2

0

0

These are referred to as the first-order conditions.

2 x ) ∂ x 1 , ∂ f ( x ∗ 1 ∗ 2 x

The Envelope Theorem

Envelope Theorem: concerns how the optimal value for a particular function changes when a parameter of the function changes

provides a shortcut to calculate the effect of changing a parameter on the value of a function

e.g., the effects of changing the market price of a commodity will have on an individual’s purchases

Example: y = x 2 + ax

Function represents an inverted parabola

Optimal values of x (x ) depend on the parameter a

Value of a

Value of x

Value of y

0

0

0

1

1

1

2

4

2

1

1

3

3

9

2

4

4

2

4

5

5

25

2

4

6

3

9

1 1 2 4 2 1 1 3 3 9 2 4 4 2 4 5

The Envelope Theorem - Direct Approach

y = x 2 + ax

First: Calculate the slope

which implies:

dy

dx

= 2x + a = 0

x = a

2

Second: substitute x into the original function

y

=

=

=

(x ) 2 + ax

a 2

4

a

2

2 + a

a

2

into the original function y ∗ = = = − ( x ∗ ) 2 +

The Envelope Theorem - Shortcut

Envelope Theorem states: for small changes in a, dy can be

da

computed by holding x constant at its optimal value x = simply calculating y from the objective function directly

First:

a

y

a

= x

a

2

and

Second: evaluate at x :

y

a

x =a/2

= a

2

Note: this is the same results obtained earlier

Envelope Theorem: states the change in the optimal value of a function (with respect to a parameter) can be found by partially

differentiating the objective function while holding x constant at its

optimal value dy

= y

a

da

{x = x (a)}

objective function while holding x constant at its optimal value dy ∗ = ∂ y ∂

Constrained Optimization

Constrained Optimization

Constrained Optimization

Constrained Optimization: finding a maximum or minimum of some function over a restricted values for (x 1 , x 2 )

The notation:

max

x 1 ,x 2

such that

f(x 1 , x 2 )

g(x 1 , x 2 ) = c.

objective function: f (x 1 , x 2 )

constraint function: g(x 1 , x 2 ) = c Interpretation:

find x

1

and x

2

such that f (x

1

) f(x 1 , x 2 ) for all values of

, x

2

x 1 and x 2 that satisfy the equation g(x 1 , x 2 ) = c.

, x 2 ) for all values of , x 2 x 1 and x 2

Solving Constrained Optimization

Assume a linear constraint function:

g(x 1 , x 2 ) = p 1 x 1 + p 2 x 2 = c

Constrained Maximization Problem

max

x 1 ,x 2

such that

f(x 1 , x 2 )

p 1 x 1 + p 2 x 2 = c.

There are two ways to solve this problem:

1. Direct Substitution

2. Lagrange Method

1 x 1 + p 2 x 2 = c . There are two ways to

Direct Substitution

1. Solve the constraint for one variable:

x 2 (x 1 ) =

c

p

2

p

p 2 x 1

1

2. Substitute x 2 (x 1 ) into the objective function:

f(x 1 ,

c

p

2

p

1

p 2 x 1 )

3. Solve the unconstrained maximization problem:

max

x

1

(F.O.C.)

c

p

2

p

1

f(x 1 ,

f(x 1 , x 2 (x 1 )) + f(x 1 , x 2 (x 1 )) x 2

p 2 x 1 )

x 1

x 2

x 1

= 0

( x 1 )) + ∂ f ( x 1 , x 2 ( x 1

Lagrange Method

Solves the constrained maximization problem by using Lagrange multipliers.

define an auxiliary function known as the Lagrangian:

L = f(x 1 , x 2 ) λ(p 1 x 1 + p 2 x 2 c)

the new variable (λ) is the Lagrange multiplier

The Lagrange method says that an optimal choice (x satisfy three first-order conditions

1

L

f(x

1

2

, x

)

x 1

L

x 2

x 2

= λp 1 = 0

x 1

f(x

1

2

, x

)

= λp 2 = 0

λ L = p 1 x

1

+

2

p 2 x

c = 0

2

, x

) must

(1)

(2)

(3)

λ p 2 = 0 − ∂ λ ∂ L = p 1 x ∗ 1

EC270: Microeconomic Theory I

.

Chapter 2 Mathematics for Microeconomics

Dr. Logan McLeod, PhD

Wilfrid Laurier University, School of Business & Economics

September 4, 2014

for Microeconomics Dr. Logan McLeod, PhD Wilfrid Laurier University, School of Business & Economics September 4,